Extension de la mandarina "Clementina" (Citrus reticulata Blanco) en la empresa citricola "Victoria de Giron" - Bello, L.=700 1 Mas, O.; Perez, R.; Rios, A.
(En, Es)
ilus., 11 ref.
Keywords: MANDARINA; PORTAINJERTOS; PLANTACION; ESPACIAMIENTO; CUBA